Analisis Implementasi Pernyataan Standar Akuntansi Keuangan (PSAK) 105 pada Pembiayaan Mudharabah - Triyana Hasibuan, Henny (E-Jurnal Akuntansi, 2020)
The purpose of this study was to analyze the implementation of PAK 105 in mudharabah financing at PT. Bank  Muamalat Indonesia Denpasar Branch in 2020. The research method used was a qualitative research method. The results showed, The recognition process at PT. Bank Muamalat Indonesia Tbk. Adapted to generally accepted standards, namely PSAK No. 105, Measurement of investment in PT. Bank Muamalat Indonesia Tbk. in cash, measured at the amount paid in accordance with PSAK 105, Presentation of mudharabah financing at PT. Bank Muamalat Indonesia Tbk. presented in the balance sheet on the element of assets equal to bank bills to customers and in accordance with PSAK 105, mudharabah financing disclosed by PT. Bank Muamalat Indonesia Tbk in the financial statements and notes to the financial statements in accordance with PSAK 105. Keywords: Accounting Treatment; Mudharabah Financing; PSAK No. 105.